2016
DOI: 10.1111/gcb.13309
|View full text |Cite
|
Sign up to set email alerts
|

Declining water yield from forested mountain watersheds in response to climate change and forest mesophication

Abstract: Climate change and forest disturbances are threatening the ability of forested mountain watersheds to provide the clean, reliable, and abundant fresh water necessary to support aquatic ecosystems and a growing human population. Here, we used 76 years of water yield, climate, and field plot vegetation measurements in six unmanaged, reference watersheds in the southern Appalachian Mountains of North Carolina, USA to determine whether water yield has changed over time, and to examine and attribute the causal mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 84 publications
(132 reference statements)
3
79
0
1
Order By: Relevance
“…Even as the ESMs project increasing precipitation and temperature, we see the variability in responses through the cascade of scale and land cover variability. This finding is consistent with other studies that observed that variability (forest cover composition and topography) in the area and size of forest-shrub conversion can buffer responses of streamflow or evapotranspiration shifts from climate change (Winkler et al, 2014;Caldwell et al, 2016).…”
Section: Changing Streamflow and Water Balancessupporting
confidence: 93%
See 3 more Smart Citations
“…Even as the ESMs project increasing precipitation and temperature, we see the variability in responses through the cascade of scale and land cover variability. This finding is consistent with other studies that observed that variability (forest cover composition and topography) in the area and size of forest-shrub conversion can buffer responses of streamflow or evapotranspiration shifts from climate change (Winkler et al, 2014;Caldwell et al, 2016).…”
Section: Changing Streamflow and Water Balancessupporting
confidence: 93%
“…Studies pointing towards increased streamflow also broadly found evapotranspiration from the canopy decreased, leading to an increase in runoff. However, work based on observations across scales and encompassing multiple disturbances indicates that the regrowth potential for understory, such as shrubs used in this study, is high and that the regrowth is a major controlling factor for water availability and direction of change for evapotranspiration and runoff (Caldwell et al, 2016;Biederman et al, , 2015Brown et al, 2014;Pribulick et al, 2016). Moreover, ecologists project that global forest covers are expected to decline and be replaced with species and understory compositions that are more water intensive.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For example, in many temperate forest communities in the eastern United States (U.S.), recent decreases in the abundance of oak species have been associated with impacts on biodiversity, wildlife habitat, and water quantity (Fralish 2004;Nowacki and Abrams 2008;Hanberry 2013;Hiers et al 2014;Caldwell et al 2016). Because changes in tree species composition can affect forest functions in these ways, characterizing species composition of existing forest communities is important for understanding the functions of those communities (Tierney et al 2009; Thompson et al 2013).…”
Section: Introductionmentioning
confidence: 99%